Changes over Time in Population Level Transport Satisfaction and Mode of Travel: A Repeat Cross-Sectional Study over a 13 Year Period, UK. (June 2017) - Olsen, Jonathan; MacDonald, Laura; Ellaway, Anne
Abstract : Background: Understanding transport satisfaction can inform national and local policy aimed at providing a sustainable transport infrastructure, which can have important national and international benefits for both health and the environment. The aim of the study was to examine changes over time in satisfaction with usual transport mode, explore individual and area level characteristics as mediators in the likelihood of transport satisfaction, and whether any changes in transport satisfaction varied by these factors over time. Methods: Adults from West Central Scotland, United Kingdom, who participated at both waves of the repeat cross-sectional 'Transport, Health and Well-being Study' conducted in 1997 (n=2735) and 2010 (n=2024) were assessed. Individuals completed a detailed postal questionnaire at both time points including self-rated satisfaction with usual transport mode (using a seven point scale subsequently dichotomised to a binary outcome of satisfied (1-2) and other (3-7)). Participants reported usual transport mode for travel to the following various destinations or events: day out, evening out, health appointment, sports facility, visiting friends/family, taking children to school, supermarket, and work/education . A multilevel logistic regression model was used and individuals were nested within areas (c.4, 000 population). The dependent (outcome variable) was transport satisfaction (binary yes/no) and the independent covariates were travel mode, age, sex, health status, access to car, urban/rural classification, and socio-economic status. Results: At the 2010 sweep, two thirds (n=1345) of individuals were satisfied with their transport choice. Those with fair/poor health were less satisfied with their usual transport compared to those in better health (Odds Ratio (OR) 0.49, p<0.001). Access to a car was associated with overall transport satisfaction (OR 2.63, p<0.001) and the effect of deprivation on transport satisfaction was mitigated when adjusted by household car access. Transport satisfaction increased more from 1997 to 2010 for retired individuals compared to those in employment (OR 1.40, p=0.032), and for those who travelled by public transport (OR 2.39, p=0.005) and using multiple modes (OR 2.19, p<0.001) compared to those who travelled by car. Conclusions: The proportion of those who travelled using public transport, active modes or by multiple mode increased journey satisfaction over time at a greater rate than those travelled by car, highlighting that continued efforts should be made to promote these more active transport modes which have potential to impact on health.